Financial Performance Analysis of PT Fast Food Indonesia (KFC) between 2016 to 2023 - Nur Fitri Amaliah; Agusdiwana Suarni; Abdul Khaliq (IECON, 2024)
The objective of this study is to evaluate the financial performance of PT Fast Food Indonesia (KFC) over an eight-year span by examining important financial ratios to determine the company's financial health and operational efficiency. The study utilizes quantitative analysis with SPSS statistical software to analyse financial data obtained from annual reports spanning 2016 to 2023. The research examines three major financial ratios: return on assets (ROA), current ratio, and debt-to-equity ratio (DER). Findings: The research indicates that PT Fast Food Indonesia has diverse financial performance trends. The ROA averaged 7.25%, displaying considerable volatility as it declined to 2% in 2022 before rebounding to 11% in 2023. The current ratio saw a steady decline from 1.90 in 2018 to 0.57 in 2023, signifying deteriorating liquidity. The debt-to-equity ratio averaged 1.8575, indicating significant dependence on debt funding. This research offers significant insights for stakeholders, such as investors, management, and financial analysts, about KFC Indonesia's financial stability and operational effectiveness. The results can inform strategic decision-making and identify areas necessitating managerial focus. This study enhances the current literature by delivering a thorough statistical analysis of KFC Indonesia's financial performance with SPSS, thereby furnishing stakeholders with in-depth insights into the company's financial trends and patterns over an extended timeframe. The study facilitates the identification of financial strengths and opportunities for enhancement within the company's operations.